Representations of canonical anticommutation relations with orthogonality condition - Yakymiv, R. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We study the class of Hilbert space representations of the ∗-algebra A^(d)_0 generated by relations of the form A^(d)_0 = Ca_j, a_j^* | a_j^* a_j = 1 - a_j a_j^*, a_j, a_j^* = 0, i eq j, i, j = 1,...,d, Namely, we describe the classes of unitary equivalence of irreducible representations of A^(d)_0 such that there exists j = 1,...,d for which a^2_j eq 0.